Pembayaran Ganti Rugi Atas Kontrak Transportasi Antarkota Perhajian dan Kesesuaianya dengan Fatwa DSN-MUI No. 43/DSN MUI/VIII/2004 Tentang Ganti Rugi (TA‘WĪD̩) : Studi Kasus pada KUH di Jeddah, Arab Saudi - Rahmi Khotijah; Syarif Hidayatullah; Endy Astiwara; Taufiq Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Intercity Pilgrimage Transportation Contract between KUH and the Rawahel company in 2019, there is a sanction article that states the amount of compensation in the form of a percentage (%) of the bus rental fee based on the number of pilgrims if certain violations occur. There is an inconsistency between the Contract and Fatwa DSN-MUI No.43/DSN-MUI/VIII/2004 concerning Compensation (Ta'wīd̩). This type of research is qualitative with a case study and empirical juridical in nature, which is research focused on analyzing the suitability of Fatwa on Compensation (Ta'wīd̩) with the payment of compensation for the Intercity Transportation Contract between KUH and Rawahel Company. The result of this study is that the determination of the amount of compensation in the Contract is not in accordance with the Fatwa so that the implementation of compensation payments by the Rawahel company against KUH has not fulfilled the principle of compensation as stipulated in the Fatwa, which is prohibited from calculating the loss that is expected to occur (potential loss).